2017
DOI: 10.1634/theoncologist.2017-0094
|View full text |Cite
|
Sign up to set email alerts
|

“Rather one more chemo than one less…”: Oncologists and Oncology Nurses’ Reasons for Aggressive Treatment of Young Adults with Advanced Cancer

Abstract: This study identifies two ethical and one psychological reasons for patients' overtreatment: 1) patients' preference for further treatment; 2) oncologists' perception of un-fairness of dying young; and 3) identification and emotional entanglement with patient. These findings emphasize the need for oncologists' awareness of the reasons guiding their treatment decisions - a sole focus on patients' preferences and on the fighting against the unfairness of dying young might lead to neglecting obligations of non-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
0
22
0
3
Order By: Relevance
“…Continuation of treatment until close to death was considered a major contributor to hospital death in our study, though often perceived as unavoidable, particularly in younger patients receiving intensive chemotherapy for aggressive disease. Administration of treatment close to death is considered overly aggressive by some ( Beaussant et al, 2018 ; Hui et al, 2014 ), but may be due to haematologists’ concerns that the potential for cure still exists (even in advanced disease), the availability of multiple and/or new lines of treatment and difficulty identifying refractory disease and the end of life phase ( Hui et al, 2015 ; McCaughan et al, 2017 ; Odejide et al, 2014 ); it may also be based on often unrealistic hope for response or cure, driven by patients and clinicians, as described in our own study and elsewhere ( Laryionava et al, 2018 ; Odejide et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…Continuation of treatment until close to death was considered a major contributor to hospital death in our study, though often perceived as unavoidable, particularly in younger patients receiving intensive chemotherapy for aggressive disease. Administration of treatment close to death is considered overly aggressive by some ( Beaussant et al, 2018 ; Hui et al, 2014 ), but may be due to haematologists’ concerns that the potential for cure still exists (even in advanced disease), the availability of multiple and/or new lines of treatment and difficulty identifying refractory disease and the end of life phase ( Hui et al, 2015 ; McCaughan et al, 2017 ; Odejide et al, 2014 ); it may also be based on often unrealistic hope for response or cure, driven by patients and clinicians, as described in our own study and elsewhere ( Laryionava et al, 2018 ; Odejide et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…This proximity intensified the sense of tragedy because of memories HCPs possess of their own younger years or their children's young adulthood and reflects countertransference, a theory that has been used to explain why HCPs may be more inclined to administer tumor-directed therapy to AYAs close to death. 22 Countertransference describes how certain emotional and behavioral reactions from HCPs toward their patients originate from previous life experiences. 23 In our study, participant reactions to their AYA patients may have originated from their own experiences as young adults or as parents of young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive treatment is more common among younger patients with cancer, which may be driven by the injustice of death at a young age. 30,31 Many participants considered QoL to be more important than LoL, and two-thirds of elderly patients (aged !65 years) indicated that QoL was at least equally as important as LoL. This finding is particularly important for designing clinical trials in advanced STS, where QoL could be considered as a (co)primary or composite endpoint.…”
Section: Discussionmentioning
confidence: 99%